Role of cytoskeletal mechanics and cell membrane fluidity in the intracellular delivery of molecules mediated by laser‐activated carbon nanoparticles. Issue 10 (11th July 2017) - Holguin, Stefany Y.; Anderson, Caleb F.; Thadhani, Naresh N.; Prausnitz, Mark R.
ABSTRACT: Exposure of cells and nanoparticles to near‐infrared nanosecond pulsed laser light can lead to efficient intracellular delivery of molecules while maintaining high cell viability by a photoacoustic phenomenon known as transient nanoparticle energy transduction (TNET). Here, we examined the influence of cytoskeletal mechanics and plasma membrane fluidity on intracellular uptake of molecules and loss of cell viability due to TNET. We found that destabilization of actin filaments using latrunculin A led to greater uptake of molecules and less viability loss caused by TNET. Stabilization of actin filaments using jasplakinolide had no significant effect on uptake or viability loss caused by TNET. To study the role of plasma membrane fluidity, we increased fluidity by depletion of membrane cholesterol using methyl‐β‐cyclodextrin and decreased fluidity by enrichment of the membrane with cholesterol using water‐soluble cholesterol. Neither of these membrane fluidity changes significantly altered cellular uptake or viability loss caused by TNET. We conclude that weakening mechanical integrity of the cytoskeleton can increase intracellular uptake and decrease loss of cell viability, while plasma membrane fluidity does not appear to play a significant role in uptake or viability loss caused by TNET. The positive effects of cytoskeletal weakening may be due to an enhanced ability of the cell to recover from the effects of TNET and maintain viability. Biotechnol. Bioeng. 2017;114: 2390–2399. © 2017 Wiley Periodicals, Inc. Abstract : In this study, we investigate the biophysical interaction of cells and energy transfer from laser‐activated carbon nanoparticles due to transient nanoparticle energy transduction (TNET). We show that weakening the cytoskeleton enabled significantly higher intracellular uptake and lower viability loss due to TNET, whereas altered plasma membrane fluidity did not significantly change resulting bioeffects. We conclude that TNET is a novel platform for intracellular delivery of molecules into cells and that cytoskeletal weakening increases uptake while reducing viability loss.